2020
DOI: 10.1298/ptr.e10007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of voluntary cough function in community - dwelling elderly and its association with physical fitness

Abstract: Objective: To compare the association of cough peak flow (CPF) with aging in communitydwelling older adults and to investigate the relationship between physical fitness and CPF in these individuals. Method: Two hundred twenty two community-dwelling older adults were enrolled. CPF was assessed as a cough function parameter. Forced vital capacity (FVC) and forced expiratory volume in 1 s (FEV1.0) were assessed as respiratory function. Maximal expiratory pressure (MEP) and inspiratory pressure (MIP) were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Physical inactivity and poor physical performance may affect respiratory and peripheral muscle, resulting in deterioration cough strength. [30][31][32] Therefore, future research are needed to clarify the causes of impaired cough in patients with PCD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical inactivity and poor physical performance may affect respiratory and peripheral muscle, resulting in deterioration cough strength. [30][31][32] Therefore, future research are needed to clarify the causes of impaired cough in patients with PCD.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it was previously shown that cough strength was related to physical performance, exercise capacity, and functional level in the elderly. Physical inactivity and poor physical performance may affect respiratory and peripheral muscle, resulting in deterioration cough strength 30–32 . Therefore, future research are needed to clarify the causes of impaired cough in patients with PCD.…”
Section: Discussionmentioning
confidence: 99%